Repeated empathy: A phenomenological description - Sánchez Muñoz, Rubén (Pensamiento. Revista de Investigación e Información Filosófica, 2023)
In a couple of excerpts from her doctoral thesis Zum Problem der Einfühlung, Edith Stein gives indications about a phenomenon she calls «repeated empathy» (iterierter Einfühlung) to distinguish it from the «reflective sympathy» (reflexive Simpathie) of Theodor Lips. In this paper we attempt to understand what repeated empathy is. In our opinion this phenomenon is fundamental for a greater understanding of intersubjectivity, since in repeated empathy we have access to alien experiences in which we see ourselves through the gaze of others. So in this phenomenon we see ourselves as another sees us. The purpose of this approaching essay is to lay the foundations of this phenomenon by clarifying its meaning.